Portuguese Abolition in British Perspective - Drescher, Seymour (Africana Studia, 2020)
The endings of the slave trade and slavery required a fundamental shift in attitudes and behavior. Sooner or later all slavesponsoring empires reconceived the institution primarily from a wealth producing to a criminal activity. This paper considers the paradigmatic shift in the two most important European slave empires Great Britain and Portugal. Assessing - the timing and the intensity of the shift requires viewing the British and Portuguese cases from both a comparative and an interactive perspective. The paper attempts to analyze the reasons why the British national shift occurred earlier, more massively and more intensely than the Portuguese. Keywords: abolitionism; Britain; civil society; honor